Thermo-hydraulic design of a multi-tube heat exchanger for methanol heating. - Pérez Sánchez , Amaury; Sarduy Rodríguez, Zamira María; Alfaro Martínez, Arlenis Cristina; Ranero González, Elizabeth; Pérez Sánchez, Eddy Javier (Ingeniería Química y Desarrollo, 2025)
A type of heat exchanger that has gained adequate attention owing to its simplicity, robustness and extensive variety of applications is the multi-tube heat exchanger. In the present work a multi-tube heat exchanger was designed form the thermo-hydraulic point of view, in order to heat a methanol stream to 60 ºC using water condensate as the heat transfer agent. To design this equipment, a classical, well known calculation methodology was employed, where several important design parameters were calculated such as the overall heat transfer coefficient (575.17 W/m2.K), the required heat exchange area (2.025 m2) and the Log Mean Temperature Difference (38.02 ºC). The calculated pressure drop values of the methanol and water streams were 3,257.66 Pa and 752.88 Pa, respectively, which are lower than the maximum limits set by the heat exchange service for both streams. The designed multi-tube heat exchanger will present a total length of 5.76 m.